Wettability Alteration Induced by Surface Roughening During Low Salinity Waterflooding - Marhaendrajana, Taufan; Ridwan, Muhammad Ghifari; Kamil, Maulana Insan; Permadi, Pudji (Journal of Engineering and Technological Sciences, 2018)
Wettability alteration during low salinity waterflooding (LSW) is expected to be one of the prominent reasons for enhanced oil recovery. However, the underlying mechanisms of improved oil recovery in sandstone during LSW are not entirely clear. Thus, a series of experiments was carried out to investigate the underlying mechanisms that drive the wettability alteration. FTIR spectroscopy was combined with thermogravimetric analysis to quantify the amount of adsorbed hydrocarbon components in sandstone with various clay contents. Afterward, the time-dependent contact angle in fabricated sandstone substrate (RMS roughness 9.911.31) was observed with various clay and brine contents to monitor the wettability alteration during LSW. The existence of divalent ions (Ca2+ and Mg2+) was found to stabilize the sandstone and prevent it from swelling. Surprisingly, with the presence of divalent ions, the rate of contact angle change was insignificant (, even though a reduction of divalent ions occurred and the rate of contact angle change with the sole presence of NaCl was notably altered (. Furthermore, the presence of higher clay content showed an increased contact angle alteration. We propose that these phenomena are partially driven by macroscopic phenomena of clay swelling, which leads to surface roughening and enhances the water-wetness.